Pembelajaran Sejarah Berbasis Kurikulum 2013 di SMA Kotamadya Jakarta Timur - Zia Ulhaq (Jurnal Pendidikan Sejarah, 2017)
This study aims to obtain a systematic description of the implementation of the 2013curriculum on learning history in high school East Jakarta Municipality. The research location is inSMAN 81 Jakarta and SMA Angkasa 1 Jakarta. This research uses qualitative approach with methodof grounded theory of research data. The results showed that the understanding of teachers in thegrassroot on various learning concepts both in terms of planning, implementation to evaluation isquite low. From the planning, implementation and assessment, only the implementation of learningthat can be implemented by teachers in the research location, while planning and assessment is notimplemented optimally. showing by teachers not making the completely lesson plan, teachers assumetwo subjects of history in secondary school (history of Indonesia and history) are the same subjects, aswell as the use of attitude assessment techniques that only use observation techniques. In addition, itwas also found out that historical learning in the research sites has been based on commucication andinformation technology in accordance with the saintifik approach in the curriculum of 2013.